Pengaruh Model Project Based Learning dengan Bantuan Media Serbaneka (Realita) terhadap Keterampilan Menulis Puisi pada Siswa Kelas VII SMPN 1 Jombang - Okta Fitriana; Andri Pitoyo; Sujarwoko Sujarwoko (Lembaga Yasin AlSys, 2026)
Although Project-Based Learning has been widely studied in language learning, studies that specifically analyze the effect of this model with the assistance of assorted media or realia on students’ poetry writing skills remain limited. This study aims to measure the effect of the Project-Based Learning model assisted by assorted media on the poetry writing skills of Grade VII students at SMPN 1 Jombang. This study used a quantitative approach with an experimental method to compare students’ writing results before and after the treatment. The research sample was drawn from Grade VII students selected using random sampling, with class VII C as the control class and class VII D as the experimental class. Data were collected through interviews, observation, and pretest and posttest assessments. The data were analyzed using descriptive statistics, normality tests, homogeneity tests, and hypothesis testing with the assistance of SPSS version 31. The results showed a significant difference between the results before and after the treatment, indicating that the Project-Based Learning model assisted by assorted media had an effect on students’ poetry writing skills. The conclusion of this study affirms that the use of Project-Based Learning supported by assorted media can serve as an effective learning alternative for improving poetry writing skills at the junior high school level. The implications of this study encourage teachers and educational institutions to further develop project-based learning in poetry writing instruction and to expand academic studies on the application of this model in Indonesian language learning.